STUDI LITERATUR: PENERAPAN KOMUNIKASI TERAPEUTIK TERHADAP PSIKOLOGIS LANSIA - Kio, Alfiery Leda; Priastana, I Ketut Andika (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Elderly is the last period in human life. The elderly have various health problems related to the aging process, one of which is psychological disorders. Efforts to improve the psychological health of the elderly can be done in various ways, one of the efforts that can be done is by applying therapeutic communication. This study aims to determine the application of therapeutic communication to the psychology of the elderly. The research method uses the Literature Review method with secondary data collection from scientific research articles from 2011-2021. Search data using Google Scholar, Crossref, Indonesia OneSearch and Garuda databases online using key words namely therapeutic communication, psychological, elderly. The articles obtained were 184 articles, but only 5 articles that matched the inclusion criteria. Selected articles are then evaluated. This literature study found that therapeutic communication has a positive impact in reducing psychological disorders in the elderly including anxiety, depression levels, and cognitive disorders. Therapeutic communication used by nurses has characteristics, namely attention, planned communication, to know, observation, appreciation and humor, taboo communication, respect, care, clarity, empathy and building relationships. Nurses are very important in implementing therapeutic communication in carrying out nursing services, especially for the elderly who experience psychological disorders to rebuild interpersonal relationships with the elderly so that the elderly are able to improve psychological conditions to an optimal stage to achieve a good quality of life in old age.